Lifecourse socioeconomic position and cohort differences in health expectancy in Australia: a longitudinal cohort study - Richard Tawiah, PhD; Carol Jagger, ProfPhD; Kaarin J Anstey, ProfPhD; Kim M Kiely, PhD (Elsevier, 2022)
Summary: Background: There is a need to know how changes in health expectancy differ for population subgroups globally. The aim of this study was to estimate 10-year trends in health expectancies by individual markers of socioeconomic position from three points over the lifecourse, evaluating how compression and expansion of morbidity have varied within a national population. Methods: We analysed data from two cohorts of the Household Income and Labour Dynamics in Australia survey. The cohorts were followed annually from 2001 to 2007 (n=4720; baseline age range 50-100 years) and 2011 to 2017 (n=6632; baseline age range 50-99 years). Health expectancies were estimated at age 65 years for four outcomes reflecting activity limitations, disability, perceived health, and mental health. Cohort differences were compared by gender, age left school, occupational prestige, and housing tenure. Findings: Women with low socioeconomic position were the only group with no improvements in life expectancy across the two cohorts. Among men with low education and all women gains in life expectancy comprised entirely of years lived with global activity limitations. Compression of years lived with severe-disability, poor self-rated health, and poor mental health was most consistently observed for men and women with high education and home ownership. Occupational prestige did not greatly differentiate cohort differences in health expectancies. Interpretation: Over the past two decades in Australia, social disparities in health expectancies have at least been maintained, and have increased for some outcomes. Equitable gains in health expectancies should be a major public health goal, and will help support sustainable health and social care systems. Funding: Australian Research Council.